An Adolescent Female with a Resistant Barking Cough: Challenges Faced in Diagnosis and Management - Aakanksha Kharb; Anand Agrawal; Sunny Garg; Devinder Kumar; Jogender Singh (Journal of Advanced Lung Health)
Somatic cough syndrome is a frequently overlooked cause of chronic cough. Most cases are concentrated in the pediatric or adolescent age groups. This case report describes a 16-year-old female suffering from somatic cough syndrome. The patient presented with complaints of cough for the past 9 months which was sudden in onset, progressive, nonproductive, and interfering with her daily routine activities and had a characteristic barking feature. Her general physical, systemic examination, and investigations were unremarkable. She did not show improvement with multiple trials of bronchodilators, antitussive medications, and antibiotics. On psychiatric evaluation, it was found that 9 months back, the patient had a stressful event at school. Then, she was started on suggestion therapy, and later, psychotropics were also added. As there was only mild improvement, the patient was planned for cerebral aversion to electrical stimuli. She showed significant improvement after the three sessions. Her response was sustained for the next year on follow-ups. This case emphasizes the need for a multidisciplinary approach for the early detection, and management of this challenging illness for better results for such patients.